Physical Chemical Properties and Antibacterial Activity of Kefir of Goat Milk Combined with Red Dragon Fruit Juice - Sri Mulyaningsih; Fikriyah Sofa Nafiah (Wahana, 2024)
Kefir is a probiotic drink made from fermented milk that is beneficial for health, including helping to maintain digestive health. Dragon fruit is rich in nutritional content and has various biological activities. This study was purposed to evaluate the physical chemical properties and antibacterial activity of goat milk kefir with combination of red dragon fruit juice against Salmonella typhi. Goat milk kefir with 6% kefir grain plus red dragon fruit juice with concentration variation of 10%, 15%, 20%. The fermentation results showed the pH value of goat milk kefir was 3.84 while the pH of kefir with combination of red dragon fruit juice ranged from 3.51-3.80 by producing total acid of 0.74-1.11%. The diameter of the inhibition zone of goat milk kefir without the addition of red dragon fruit juice is 9.0 mm and goat milk kefir with the addition of red dragon fruit juice with concentrations of 10%, 15%, 20% were 10.2; 10.7; 12.0 mm respectively. The goat milk kefir with 20% red dragon fruit juice combination had the greatest antibacterial activity. The addition of red dragon fruit juice in goat milk kefir affected its organoleptically, chemical physical properties and increased the antibacterial activity.